Implementation of the Electronic Licensing Service Program in Public Service at Bengkulu Province - Tomimi, Zahran Mabrukah; Prasetyo, Imam Try (University of Merdeka Malang, 2024)
Along with the wishes of the people who expect public services to run more effectively because the most important task of government agencies is the service provider, but effectiveness is also very important and needed in supporting services. And one of the government agencies in providing services is the Bengkulu Province One-Stop Investment and Integrated Service Office, the services provided use an online system called the Electronic Licensing Service System.Â The purpose of this study was to determine the effectiveness of licensing services carried out online provided by the Bengkulu Province One-Stop Investment and Integrated Services Office. This research uses descriptive qualitative method by using 3 elements namely Capacity, Support, and Value. The results of the research are the existence of support from the Bengkulu Province One-Stop Investment and Integrated Services Office in allocating resources in the form of financial, human and infrastructure. Then the availability of infrastructure resources in the form of equipment such as computers, printers and internet networks that complement this Electronic Licensing Service System. When the system was implemented, there was an increase in service quality that affected the satisfaction of the people of Bengkulu Province with the services provided as evidenced by the reduction in complaints from the Community Satisfaction Survey from 90.86% to 90.27%. So it can be concluded that the implementation of the Electronic Licensing Service System in Public Services at the One-Stop Investment and Integrated Services Office that the implementation of the system has gone well, with the support of leadership, resources, infrastructure, socialization, availability of infrastructure resources, and people. And the benefits of implementing this system are also felt by the community related to improving the quality and effectiveness of public services provided.